2018
DOI: 10.1007/s12098-018-2722-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Invasive Fungal Infections in Children with Persistent Febrile Neutropenia Treated for Acute Leukemia – A Prospective Study

Abstract: Thus, prevalence of IFI is very high in children with persistent febrile neutropenia who are not on antifungal prophylaxis. Abnormal chest x- ray and clinical sinusitis are important predictors of IFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 13 publications
6
27
2
1
Order By: Relevance
“…Clinical presentations associated with IFD include sinusitis and abdominal discomfort. 5 However, abdominal pain and pneumonia predominated in our study. Nevertheless, respiratory distress, oxygen requirement, and hypotension have been documented as high risk factors of FN in developing serious morbidity.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Clinical presentations associated with IFD include sinusitis and abdominal discomfort. 5 However, abdominal pain and pneumonia predominated in our study. Nevertheless, respiratory distress, oxygen requirement, and hypotension have been documented as high risk factors of FN in developing serious morbidity.…”
Section: Discussioncontrasting
confidence: 48%
“… 9 , 28 These are usually reported among patients with mostly hematologic malignancies in most studies. 5 , 9 In addition, most previous studies on pediatric oncology populations have included nonfever or nonneutropenic cases. 26 In our study, cancer types were not associated with IFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that abnormal chest x-ray and clinical sinusitis are important predictors of invasive candidiasis in these patients, and protocols that include early empirical antifungal therapy covering this infection is essential. 93 Thus, as noted, prophylaxis may be effective in reducing the rate of disseminated candidiasis in people with leukemia, but long-term use of antifungal drugs may impose some difficulties, and the results of some studies have shown that despite prophylaxis, IFI has occurred in patients with blood malignancies.…”
Section: Dovepressmentioning
confidence: 98%
“…While the frequency of Aspergillus spp. isolation in lung samples has been rising according to multiple studies [25,40,41], the incidence of Pneumocystis jirovecii pneumonia has dropped significantly since effective chemoprophylaxis with co-trimoxazole was established in children undergoing chemotherapy for hematologic malignancies [42,43].…”
Section: Identified Causesmentioning
confidence: 99%